2014
DOI: 10.3109/03008207.2014.910199
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of cranial cruciate ligament rupture (CCLR) in dogs

Abstract: Cranial Cruciate Ligament rupture (CCLR) is one of the most common forms of lameness in dogs and is analogous to rupture of the anterior cruciate ligament in humans, for which it can serve as a model. As there is a strong breed-related predisposition to CCLR in dogs, a study was undertaken to consider putative genetic components in susceptible dog breeds. A candidate gene, single nucleotide polymorphism (SNP) genotyping approach using MALDI-TOF mass spectrometry (Sequenom Ltd) was designed to investigate sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…183 Using a genome-wide association study design, the same investigators 184 have also identified 3 main chromosomal regions, which include variants within neurologic pathway genes, associated with canine cranial cruciate ligament rupture.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…183 Using a genome-wide association study design, the same investigators 184 have also identified 3 main chromosomal regions, which include variants within neurologic pathway genes, associated with canine cranial cruciate ligament rupture.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Mixed breed dogs, as the most common breed in this study had CCL rupture at an average age of 7.7 years. Dogs aged 5 years and older had 2.5 times the odds of CCL rupture compared with dogs aged less than 5 years, P<0.01. there is a strong breed-related predisposition to CCL rupture in dogs (BaIrD, 2014). West Highland White Terriers, Yorkshire Terriers and Rottweilers had a significantly higher prevalence of CCLR, and Rottweilers had five times greater incidence compared with other pure breeds, with females twice as likely to suffer CCLr compared to males (aDaMS et al, 2011).…”
Section: Resultsmentioning
confidence: 96%
“…Breed predisposition has been detected in Neapolitan Mastiff, akita, Saint Bernard, rottweiler, Mastiff, Newfoundland, Chesapeake Bay retriever, Labrador retriever, and american Staffordshire terrier (COrr, 2009) breeds, while the Greyhound has a dramatically reduced frequency of this disorder, supporting the heritable basis of the CCL rupture trait (BaIrD et al, 2014). Increased incidence has also been detected for neutered males and females with a slight majority of females, as well as for older dogs with an average age of 7 years in an earlier study (haraSeN, 2003).…”
mentioning
confidence: 83%
“…These genes include, among others, COL5A1, COL1A1, COL3A1, COL11A1 and FBN1. 21 One GWAS has identified three main chromosomal regions associated with CCLR on chromosomes 1, 3 and 33. Interestingly, the results of this study implicate the involvement of neurological pathways in susceptibility to CCLR 22.…”
Section: Genetic Risk Factors In Other Speciesmentioning
confidence: 99%
“…1),2–8 Achilles tendon injuries (reviewed in refs. 9 and 10),4 11 12 lateral epicondylitis,13 rotator cuff injuries14–16 and carpal tunnel syndrome17–19 in humans, as well as, equine superficial digital flexor tendinopathy20 and canine cranial cruciate ligament rupture (CCLR) 21 22…”
Section: Introductionmentioning
confidence: 99%